STRATEGI MULTIKRITERIA PENGELOLAAN SUMBERDAYA HUTAN BERKELANJUTAN DI KAWASAN ARGOPURO - Suciati, Luh Putu (Jurnal Sosial Ekonomi Pertanian, 2008)
Generally, the purposes of this research is to develop multicriteria strategy for forest management in Argopuro mountain in Jember Regency in order to improve benefit for prosperity socialize and support regional development continuation. Degradation of forest significanly is influenced by the forest area managed by Perum Perhutani, the ratio of sum of the Perhutani worker amount and the amount of human resources each district. Education and the quantity of land managed by farmer influence the degree of participation in forest management. Game Theory Analysis show that forest management effort at optimum level at social and economic obtained through management by PHBM where farmer done farming in forest land, take care the wood and get sharing from Perum Perhutani. Multicriteria strategy of forest management at economic driver are PHBM with weighted at participation (social aspect), increase farmer income( economic aspect) and carbon emission to prevent of global warming (ecology aspect). Keywors  :  Forest management, Multicriteria strategy, Sustainable resource